Nonparametric estimation of regression models with mixed discrete and continuous covariates by the K-nn method. (16th March 2017) - Green, Carl; Li, Qi; Zhang, Yu Yvette
ABSTRACT: In this article we consider the problem of estimating a nonparametric conditional mean function with mixed discrete and continuous covariates by the nonparametric k -nearest-neighbor ( k-nn ) method. We derive the asymptotic normality result of the proposed estimator and use Monte Carlo simulations to demonstrate its finite sample performance. We also provide an illustrative empirical example of our method.